Burkholderia cenocepacia Infections in Cystic Fibrosis Patients: Drug Resistance and Therapeutic Approaches - Scoffone, Viola C.; Chiarelli, Laurent R.; Trespidi, Gabriele; Mentasti, Massimo; Riccardi, Giovanna; Buroni, Silvia (Frontiers in Microbiology, 2017)
Burkholderia cenocepacia is an opportunistic pathogen particularly dangerous for cystic fibrosis (CF) patients. It can cause a severe decline in CF lung function possibly developing into a life-threatening systemic infection known as cepacia syndrome. Antibiotic resistance and presence of numerous virulence determinants in the genome make B. cenocepacia extremely difficult to treat. Better understanding of its resistance profiles and mechanisms is crucial to improve management of these infections. Here we present the clinical distribution of B. cenocepacia described in the last six years and methods for identification and classification of epidemic strains. We also detail new antibiotics, clinical trials and alternative approaches reported in the literature in the last five years to tackle B. cenocepacia resistance issue. All together these findings point out the urgent need of new and alternative therapies to improve CF patients’ life expectancy.